Relationship between physical activity and cerebral white matter hyperintensity volumes in older adults with depressive symptoms and mild memory impairment: a cross-sectional study - Otsuka, Shotaro; Kikuchi, Kiyoshi; Takeshita, Yasufumi; Takada, Seiya; Tani, Akira; Sakakima, Harutoshi; Maruyama, Ikuro; Makizako, Hyuma (Frontiers in Aging Neuroscience, 2024)
Introduction Cerebral white matter hyperintensities (WMHs) are commonly found in the aging brain and have been implicated in the initiation and severity of many central nervous system diseases. Furthermore, an increased WMH volume indicates reduced brain health in older adults. This study investigated the association between WMH volume and physical activity in older adults with depressive symptoms (DS) and mild memory impairment (MMI). Factors associated with the WMH volume were also investigated. Methods A total of 57 individuals aged over 65 years with DS and MMI were included in this study. The participants underwent magnetic resonance imaging to quantify WMH volumes. After WMH volume was accumulated, normalized to the total intracranial volume (TIV), the percentage of WMH volume was calculated. In addition, all participants wore a triaxial accelerometer for 2 weeks, and the average daily physical activity and number of steps were measured. The levels of blood biomarkers including cortisol, interleukin-6 (IL-6), brain-derived insulin-like growth factor-1, and brain-derived neurotrophic factor were measured. Motor and cognitive functions were also assessed. Results Faster maximum walking speed and longer time spent engaged in moderate physical activity were associated with a smaller percent of WMH volume, whereas higher serum IL-6 levels were associated with a larger percent of WMH volume. The number of steps per day, time spent engaged in low levels of physical activity, cognitive function, and all other measured biomarkers were not significantly associated with percent of WMH volume. Discussion Higher blood inflammatory cytokine levels, shorter duration of moderate physical activity, and lower maximum walking speed were associated with a higher percent of WMH volume. Our results provide useful information for maintaining brain health in older adults at a high risk of developing dementia and may contribute to the development of preventive medicine for brain health.